Noiseless steganography : the key to covert communications - Desoky, Abdelrahman (CRC Press, 2012)
"Foreword Steganography is the science and art of covert communications and involves two procedures. First, the required message is concealed in a particular carrier, e.g., image, audio, text, etc., that is called a steganographic cover. The second procedure is concerned with transmitting the cover to the message recipient without drawing suspicion. Fundamentally, the steganographic goal is not to hinder the adversary from decoding a hidden message, but to prevent the adversary from suspecting the existence of covert communications. When using any steganographic technique if suspicion is raised, the goal of steganography is defeated regardless of whether a plaintext is revealed. Contemporary steganography approaches camouflage data as noise in a cover that is assumed to look innocent. For example, the encoded message can be embedded as alteration of digital images, audio files, and text, without noticeable degradation. However, such alteration of authenticated covers can raise suspicion and makes the message detectable. Another example is when linguistics, e.g., using synonymous words, is exploited as a means to conceal a message, causing the presence of abnormal and sometimes weird sentences in a text that become discernible by human and machine examinations. The presence of such unjustifiable noise draws attention and unravels the hidden communications. This book introduces a novel Noiseless Steganography Paradigm (Nostega). Nostega neither hides data in a noise nor produces noise. xi i Foreword Instead, it camouflages messages in a form of unquestionable data in the generated cover. In addition, steganography approaches found in the literature have focused on how to conceal a message and not on how to camouflage its transmittal"-- Provided by publisher